2013
DOI: 10.1021/ic302333e
|View full text |Cite
|
Sign up to set email alerts
|

The First Vanadate–Carbonate, K2Mn3(VO4)2(CO3): Crystal Structure and Physical Properties

Abstract: Mixed potassium-manganese vanadate-carbonate, K(2)Mn(3)(VO(4))(2)(CO(3)), represents a novel structure type; it has been synthesized hydrothermally from the system MnCl(2)-K(2)CO(3)-V(2)O(5)-H(2)O. Its hexagonal crystal structure was determined by single-crystal X-ray diffraction with a = 5.201(1) Å, c = 22.406(3) Å, space group P6(3)/m, Z = 2, ρ(c) = 3.371 g/cm(3), and R = 0.022. The layered structure of the compound can be described as a combination of honeycomb-type modules of [MnO(6)] octahedra and [VO(4)]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 16 publications
3
19
0
Order By: Relevance
“…Such edge shared 2‐D planar systems are of interest because they often display interesting magnetic properties and thus merit a more detailed examination , . We recently observed a topologically similar structure in the alkali transition metal molybdate systems, where KMn 3 (MoO 4 ) 2 O(OH) was found to have an ideal Kagome layer in space group R 3 m .…”
Section: Resultsmentioning
confidence: 94%
“…Such edge shared 2‐D planar systems are of interest because they often display interesting magnetic properties and thus merit a more detailed examination , . We recently observed a topologically similar structure in the alkali transition metal molybdate systems, where KMn 3 (MoO 4 ) 2 O(OH) was found to have an ideal Kagome layer in space group R 3 m .…”
Section: Resultsmentioning
confidence: 94%
“…The promise of fluoro-phosphates and vanadates as magnetically and electrochemically active materials has been shown in recent research [see, for example, Keates et al (2013)]. Novel materials based on phosphates with 2D and 1D subsystems of the magnetic structure, formed by first-row transition metals, show highly functional characteristics, inherent to frustration of the exchange interaction of magnetically active ions (Shvanskaya et al, 2015;Yakubovich, Kiriukhina et al, 2013;Yakubovich, Yakovleva et al, 2013). Research into the physical properties of such objects lies in the field of quantum cooperative phenomena and contributes to the development of theoretical ideas about the structure of matter (Lin & Ding, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The vanadate -carbonate system K 2 Mn 3 (VO 4 ) 2 CO 3 has been recently identified as a very promising prototype for studying magnetic frustration. [33,34] Its structure, shown in Fig. 2, consists of alternately stacked triangular and honeycomb magnetic layers.…”
Section: Introductionmentioning
confidence: 99%
“…It was inferred that divalent Mn is present in a high-spin state (S = 5/2) in the octahedral environment of the honeycomb layer and a low-spin state (S = 1/2) in the trigonal bipyramidal coordination of the Mn 2+ ions occupying the triangular layer. [33] The low-temperature magnetic transitions were attributed to the ordering of the S = 5/2 ions of the honeycomb lattice , while the S = 1/2 triangular layers were thought to remain paramagnetic. Subsequent first-principles density functional theory-based analysis showed that, contrary to the previous suggestion, both inequivalent Mn ions occupying the two layers are in high-spin S = 5/2 state.…”
Section: Introductionmentioning
confidence: 99%